2013
DOI: 10.1086/669681
|View full text |Cite
|
Sign up to set email alerts
|

Moneyspots: Extraneous Attributes and the Coexistence of Money and Interest-Bearing Nominal Bonds

Abstract: It is folklore among monetary theorists that, under laissez faire, absent ad-hoc assumptions that favor money over bonds, there do not exist equilibria in which government-issued fiat money coexists with nominal risk-free, interest-bearing government bonds with similar physical characteristics. This proposition is the basis for the strongest version of the rateof-return-dominance puzzle. In this paper I show that if-as has been the case throughout monetary history-the physical object used as fiat money is hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…From (19) and (20), we obtain = u 0 (q) r 1 and = r 1. The credit market clears.There are two cases.…”
Section: Policy and Liquidity Trapmentioning
confidence: 99%
See 1 more Smart Citation
“…From (19) and (20), we obtain = u 0 (q) r 1 and = r 1. The credit market clears.There are two cases.…”
Section: Policy and Liquidity Trapmentioning
confidence: 99%
“…In Zhu and Wallace (2007), the traders' portfolio composition of money and debt allows to select di¤erent points on the bilateral contract curve while, here, the equilibrium trade need not be in the pairwise core. Here, as in Lagos (2013), the coexistence of money and debt emerges from coordination among agents, rather than the imposition of a legal requirement. However, while in Lagos (2013) agents coordinate on the di¤erent types of money, as captured by di¤erences in their serial numbers, here coordination occurs on the type of debt, real or monetary.…”
Section: Introductionmentioning
confidence: 99%
“…2 Among recent related works using search-theoretic models of money are Aiyagari et al (1996), Shi (2005), Boel and Camera (2006), Zhu and Wallace (2007), Berentsen and Waller (2008), Marchesiani and Senesi (2009), and Lagos (2010).…”
Section: Modelmentioning
confidence: 99%
“…However, it has been observed that differences in denominations and legal restrictions are sometimes absent, and yet differences in returns survive. Lagos (2013), for instance, argues that “the legal restrictions hypothesis does not seem compelling for the present‐day United States” (p. 149). Moreover, on the legal restriction theory, liquidity traps would have to be attributed to exogenous factors, such as changes in policy or regulation, leading to the counterfactual conclusion that the public authorities would simply have to reverse the policy or regulatory change to let the economy out of the trap.…”
mentioning
confidence: 99%